Quantifying Grain Shape Characteristics and Fragmentation in Raw and Processed Frac Sand From Western Wisconsin - Blotz, Kaelyn E. (My University, 2015)
This study addresses issues including whether sand grains are fractured during processing (crushing/washing) for use in frac sand applications. If grains are fractured, what sizes of fragments are produced? It is important to determine if any of the fragments are small enough to be considered respirable. Another aspect of this study is to determine if digital analysis is a faster and more effective method to quantitatively analyze sand grain shapes.
Color poster with text, maps, images, charts, and tables.
Keywords: Hydraulic fracturing; Respiratory health; Processing; Silica; Frac sand mining; Posters